THE INFLUENCE OF WORK-LIFE QUALITY AND TRANSFORMATIONAL LEADERSHIP ON THE LECTURERS OF AKPELNI SEMARANG - Devi Kusumaningrum; Haryani; Karjono; Tini Utami (Jurnal Maritim Malahayati, 2022)
Akpelni is one of the maritime vocational higher schools which educate the candidate of seafarers in Indonesia. Therefore, this research is done to look for a solution to a problem faced by Akpelni observational Aim. This is subject to learning how to build lecture performance with enhanced quality of work life and transformational leadership as variable as free. Observational Model examination empiric utilizes regression get phase on programs SPSS version 21.00. This observational Population is all lecturers at Akpelni. Base sample requirement that representative; therefore sample amount in observational is 60 respondents with the census method. All examinee hypothesis on observational can be accepted since t test point out the result that significant. This observational result points out a positive relationship and significance between the quality of work life and lecture performance and positive influential transformational leadership and significant to lecture performance. The results showed that quality of work life is the most influential factor on lecture performance to the value of the regression coefficient of 0.459. The strategic finding in this research materializes profound managerial implications by regards various strategy push the quality of work life for lectures in achieving lecture performance. This observational recommendation is needed to step up in performing each observational variable and evaluate the resulting managerial policy utilized up to the better lecture performance.